The effect of some metal oxide nanocomposites on the pulsating heat pipe performance. (November 2021) - Hashemi, Seyed Masoud; Maleki, Ali; Ahmadi, Mohammad Hossein
Abstract: Increasing the performance of heat exchangers is one of industry's most pressing challenges. Pulsating heat pipes (PHPs), as a novel technology with high-performance, are broadly used in solar distilled water and systems solar water heaters. In the present work, the impact of three nanofluids including zirconium dioxide (ZrO2 ), bismuth ferrite (BiFeO3 )/ZrO2 (ZBF), and ZrO2 /SiO 2 composites under concentrations of 0.25, 0.5, and 1.0 g/L was investigated on the PHPs performance. The thermal resistance of the base fluid and the produced nanofluids was compared under a constant filling ratio of 50% and different input powers to the evaporator. The obtained results revealed that the use of working fluid such as nanofluids increased the heat transfer of PHPs in comparison to the base fluid and reduced the thermal resistance. Among the nanofluids used, the concentration of 0.25 g/L of the prepared nanocomposites provided the best performance. The resistance of the PHPs at some fluxes was reduced by up to 40%. In general, from the point of view of materials engineering, the structure of compounds used in nanofluids should have low thermal resistance, high thermal conductivity, and low viscosity. From a chemical point of view, using metals and compounds with high thermal conductivity is essential due to significant electron exchange. Graphical abstract: Highlights: The effect of using various nanofluids on heat pipe performance efficiently tested. BiFeO3 /ZrO2 (ZBF), ZrO2 and ZrO2 /SiO2 nanocomposites experimented as nanofluids. Thermal resistance of working fluid has been reduced up to 40%. Optimizations on the concentration of nanomaterials has been performed.